Diagnosis of liver fibrosis in patients with hepatitis B–related liver disease using ultrasound with wave-number domain attenuation coefficient - He, Danqing; Zhang, Chaoxue; Qiu, Wenqian; Xie, Qinxiu (Turkish Journal of Gastroenterology, 2020)
Background/Aims: The importance of identifying the stage of liver fibrosis has motivated the development of non-invasive methods. This study aimed to evaluate the applicability of ultrasound analysis involving the wave-number domain attenuation coefficient (W-Ac) in the non-invasive quantitative differentiation of liver fibrosis. Materials and Methods: This was a prospective study of inpatients with hepatitis B-related liver disease treated between October 2016 and January 2018. In ultrasound the echo from the near-field liver tissue was selected as the reference signal. The W-Ac of liver tissues was based on the fast Fourier transform of the acquired post-beamforming radio frequency signals. These values were compared to fibrosis from biopsyBağlantı METAVIR score results. Receiver operating characteristic (ROC) curve tested the W-Ac method.Results: Forty-six patients were enrolled, including 27 males and 19 females. Fibrosis was stage F0 in 12 patients, F1 in 13, F2 in 10, F3 in 7, and F4 in 4. W-Ac increased with the progression of liver fibrosis up to stage F3. There were differences between F0-F4 stages (P<0.001), and between any two stages of fibrosis (P<0.05), except for stages F3 and F4. There was a significant correlation between W-Ac and METAVIR score (r=0.795, P<0.001). W-Ac differed between non-fibrosis (F0) and fibrosis (F1-F4) groups (P<0.001) and in the normal (F0), early-fibrosis (F1-2), and late fibrosis groups (F3-4) (P<0.001). ROC area under the curve was 0.890, and at a cut-off of 0.12153 the sensitivity was 0.706 and specificity was 0.830.Conclusion: W-Ac allowed assessment of liver fibrosis in clinical practice.